Variation in the tracheoids of seeds from the subtribe Pithecocteniinae (Bignonieae: Bignoniaceae) and their contribution to the systematics of the group - Burelo Ramos, C.M.=700 1 Lorea Hernandez, F.G.; Angeles, G.
(Es, En)
Ilus., 24 ref.
Keywords: BIGNONACEAE; TAXONOMIA; DISTRIBUCION GEOGRAFICA; MEXICO